Second-Order Strains of Lignostone Under Creep and Constitutive Equations - Czech, M. (Engineering Transactions, 1993)
Specimens of the beech wood lignostone are tested for creep under simple tension along the grain and torsion, respectively. The second-order strains (interrelated strains) 2l12 and l11 generated in result of pure tension and torsion are found to be nonlinear. To describe that nonlinear behaviour, the nonlinear theory of visco-elasticity has been employed and the similarity of the creep curves is used. Correct description of the considered phenomena is obtained as a result.